Does Personality Influence University Students’ Public Speaking? - Atika Winari Putri; Benni Ichsanda Rahman HZ; Sholihatul Hamidah Daulay (Scope : Journal of English Language Teaching, 2022)
The point of this study is planned to research the ability of understudies in performing public speaking, in light of their personality: extrovert and introvert. This study utilized a qualitative approach where the scientist depicted the introvert and extrovert personalities of individual character of EFL students talking execution. The participants were 203 understudies from five classes of English. The data collection technique used was semi-structured. The data collected during this study was then examined using two different techniques: statistical counting for quantitative information about the introvert and extrovert traits of the students and analysis for qualitative information about the effectiveness of their public speaking. The findings show that on average, extrovert students’ accomplishments in talking are better than introverts, but not significant, however not huge. The thing that matters is simply 0.02 points among 0 to 5 in scoring. Students who are introverts or extroverts have different learning methods; introverts tend to study by themselves, while extroverts enjoy interacting with others and studying in groups.